A Study of Daylighting Impact at Inpatient Ward, Seri Manjung Hospital - Muhamad, Jamaludin; Amirul Amin Ismail; Sayed Abul Khair, Sayed Muhammad Aiman; Hayroman Ahmad (International Journal of Sustainable Construction Engineering and Technology, 2022)
Over the past few decades, there has been a growing interest in passive design strategies in the built environment, such as daylight. Using sunlight as the source, passive daylighting aims to provide effective natural lighting into the building while retaining maximum visual comfort without using mechanical equipment. Various research has shown the benefits of the natural environment to aid in human recovery, including daylighting. The majority of the biophilic design studies focused on workplace and healthcare environments such as hospital design. While biophilic architecture brings the meaning of nature to the internal environment, the positive effects of this biophilia are particularly concerned on healthcare facilities as it puts an element of extreme pressure on the space. This paper aims to understand the relationship between the patients and staffs’ experiences of their physical environment, specifically addressing the use of daylighting as aiding the recovery of patients and restorative impact for the users. This paper investigates the effects of daylighting in the inpatient ward at Seri Manjung Hospital through a set of questionnaires distributed to the 50 respondents of male and female users aged 18 and above. This inpatient ward space is built with windows and utilising natural lighting during the day. The participants were asked to share their experience on the lighting conditions in the ward space and the impact on their health and recovery. The outcome of this study has shown that passive daylighting technique and biophilic design in inpatient wards help to increase users' connectivity with nature, improve physical and psychological well-being and accelerate the recovery process. Consequently, incorporating passive daylighting and biophilic design in a healthcare setting will shift the hospital's design to be more sustainable and responsive to the environment.